Analisis Pengaruh Variasi Penambahan Fly Ash terhadap Kekuatan Tarik Komposit Serat Sabut Kelapa sebagai Alternatif Material Dinding Ruang Akomodasi Interior Kapal - Virgiana Kusuma Pratiwi; Mohamad Hakam; Widya Emilia Primaningtyas (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
Indonesia is a maritime country so that ships are transportation that supports economic movement. The government's policy of prioritizing the maritime sector in national development has a positive impact on the domestic shipping industry. The shipping industry over time considered the use of composites as a substitute for wood. This innovation is expected to be environmentally friendly because it is a way of treating waste. The lack of use of coco fiber and fly ash as plantation waste and industrial fuel combustion can be used as opportunities for new environmentally friendly raw materials. It is necessary to use coconut fiber as an alternative natural fiber to synthetic fiber as a reinforcing element from fly ash as a filler in the manufacture of composites. Coconut coir fiber as a reinforce was delignified using 5% NaOH for 120 minutes to reduce the lignin content in the fiber. Analysis of the strength of mechanical properties through tensile tests in accordance with ASTM D638-14 on composite specimens with variations in the addition of reinforcement as much as 10% and 30%, and various variations in the percentage of adding fly ash of 0%, 5%, and 15% to the reinforce. The variation of the composite mixture to the highest tensile strength was obtained by adding 30% reinforce. Specimen 9 with fly ash filler of 15% produced a tensile strength of 27.09 MPa. The mixture of adding reinforcement and filler substitution in coconut fiber composites has a strengthening effect on the tensile strength of the composite. The resulting composite can be used for bulkhead wall material for ship interior accommodation in accordance with SNI 01-4449-2006 regarding fiberboard.